snoRNA23 enhances the progression of hepatocellular carcinoma via regulation of the Wnt/β-catenin pathway - Qiao, Shengxian; Zhang, Xu; Wu, Zhichao; Zhang, Lei; Sun, Shaojie (Cellular and Molecular Biology, 2021)
Small nucleolar non-coding RNA(snoRA)23 is upregulated in human pancreatic ductal adenocarcinoma. However, to the best of our knowledge, the role of snoRA23 in hepatocellular carcinoma progression has not been determined. MTT and colony formation assays were used to assess the cell viability and proliferation of HCC cells with snoRA23 knocked down, respectively, and a lymphatic vessel formation assay was used to determine tube formation ability of Human dermal lymphatic endothelial cells treated with conditioned media from HCC cell cultures. The results showed that snoRA23 knockdown attenuated cell viability, colony formation,and lymphatic vessel formation in HCC cells. snoRA23 was correlated with the prolonged overall survival of patients with HCC. Additionally, snoRA23 knockdown downregulated the Wnt/β-catenin signaling pathway by decreasing Wnt3a expression and β-catenin levels.β-methylacyl-CoA racemase (AMACR) levels were notably decreased by snoRA23 depletion. Finally, it was confirmed that AMACR overexpression partially rescued snoRA23-modulated HCC tumorigenesis. The results of the present study provide further insight into the role of non-coding RNAs in the development and progression of HCC.